The Effectiveness of Child-Friendly Media on the Reading Interest and Ability of Elementary School Students - Rujiani Rujiani; Eko Handoyo; Edi Waluyo (Universitas Sebelas Maret, 2026)
This study examined the effectiveness of a child-friendly interactive magnetic board in improving elementary students' reading interest and early reading skills in regular and inclusive classrooms. A convergent parallel mixed-methods design was used to integrate quantitative and qualitative evidence. Participants were 12 students selected purposively from two schools: six Grade-1 students from SD Negeri Tlogowungu 02 (regular setting) and six Grade-2 students from SD Negeri Trangkil 06 (inclusive setting with diverse learning needs). Reading interest was assessed through structured observations (attention, enthusiasm, verbal response, participation), while reading skills were measured using a teacher-administered early literacy test (letter recognition, word decoding, and simple sentence reading). Quantitatively, median reading-skill scores increased from 52.0 to 78.5 in the regular class and from 45.0 to 70.0 in the inclusive class after two intervention sessions; Wilcoxon signed-rank analysis indicated improvement in both groups (p = 0.031). Qualitative findings showed higher engagement, longer on-task behavior, and increased willingness to read aloud. The interactive magnetic board functioned as a child-friendly multisensory medium (visual, auditory, tactile) that supported motivation and literacy participation, including among students with learning difficulties. The study concludes that the media is a feasible and inclusive instructional tool for early literacy instruction, while also noting the need for larger samples and longer intervention periods in future studies